HUBUNGAN ANTARA BUDAYA KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU SDIT IBNU ABBAS KORPRI KECAMATAN SUKARAME BANDARLAMPUNG - Neliyana (UNISAN JURNAL, 2024)
This research aims to describe and analyze how work culture and work motivation influence the performance of PAI SDIT Ibnu Abbas teachers and how efforts are made to improve student learning achievement. This research is qualitative field research and uses a descriptive analytical approach. Data collection was carried out using observation, interviews and documentation methods. Data analysis is carried out by giving meaning to the data collected and then drawing conclusions. Based on the results of the research analysis, the following conclusions can be drawn: 1) The relationship between work culture and the educational characteristics of SDIT Ibnu Abbas students with a significance t of 0.002 < 0.05. This means that work culture has a positive influence on the educational characteristics of SDIT Ibnu Abbas students with a percentage of 67.5%; 2) The relationship between work motivation and the educational characteristics of SDIT Ibnu Abbas students with a significance t of 0.000 < 0.05. Thus, work motivation has a positive effect on the learning achievement of SDIT Ibnu Abbas students with a percentage of 69.9%; 3) The relationship between work culture and work motivation on educational characteristics at SDIT Ibnu Abbas with a significance F of 0.002 < 0.05 with a percentage of 70.3%. By looking at the results of the significance of F in the Anova test carried out, it is known that the F value is 0.002, so it is known that Work Culture has an influence on efforts to increase Work Motivation and student learning achievement. The better the quality of Work Culture towards Work Motivation at SDIT Ibnu Abbas, the better the student learning achievement at SDIT Ibnu Abbas. Therefore, in order for student work motivation and learning achievement to increase, work culture must be implemented optimally.